Pengendalian Kualitas Dengan Pendekatan Metode Statistical Process Control, FMEA, Dan Kaizen Di PT. Surya Tsabat Mandiri - Andhyka Tyaz Nugraha; Linda Afriani; Rizqi Wahyudi (Jurnal Industri dan Inovasi (INVASI), 2025)
The research was carried out at PT. Surya Tsabat Mandiri where the company still produces an unpredictable amount of defective products each time production. The purpose of the research is to determine the level of disability, identify the cause of the disability and make suggestions for improvement. The approaches used in this study are Statistical process control (SPC), Failure Modes and Effects Analysis (FMEA) with improvement proposals using the Kaizen approach. Based on data processing results using p control maps, as many as 36 data out of control with the most commonly occurring types of faulty products such as baked bread and sliced breads. The factors causing the occurrence of defective products are human, material, machine and environmental factors. Correctional action was proposed against the failure mode that had the highest RPN value. The results of FMEA analysis on the cause of sliced bread had the maximum RPN of 288 coming from the moist bread cause. The proposed improvements are the installation of a temperature meter and the creation of a room temperature maintenance SOP. The cause of the roasted bread with RPN 288 and 240 comes from the worker's less careful and responsive and worker less cautious during the process of reversing the bread. The improvement proposal is to make a work instruction to the employee and give knowledge about the importance ofining the quality of the product.